Preferences for mental health treatment for post-partum depression among new mothers - Meital Simhi; Orly Sarid; Julie Cwikel (BMC, 2019)
Abstract Background The prevalence rate of postpartum depression (PPD) is 9 to 17% among mothers, with higher rates among low income and immigrant populations. Due to the negative effects of PPD symptoms on both the mother and baby, treating mothers with depression symptoms is of great importance. This study examined treatment preferences for PPD among Israeli mothers with and without PPD symptoms, specifically focusing on treatment centers, type of professional and mode of treatment, to help develop relevant policies to promote the health of mothers by reaching a deeper understanding of their preferences. Methods 1000 mothers who attended Maternal Child Health Clinics (MCHCs) in Israel for their infant's first medical exam participated in a cross-sectional survey. Results In this sample, 8.4% of the participants suffered from PPD. Mothers with PPD compared to those without symptoms had lower economic status, were more likely to be single, to be first-time mothers, have an unemployed partner and to have immigrated to Israel. Mothers with PPD preferred private mental health practice and community treatment centers by mental healthcare professionals. They also preferred group interventions and personal psychotherapy rather than technology-based interventions. Conclusions The study findings support the formulation of mother-sensitive health policies based on understanding mothers' preferences, and thus, help prepare treatment alternatives that will suit different groups of mothers with PPD, for the benefit of mothers, newborns, and families. Disseminating the results of this study among professionals as part of professional training, can promote appropriate treatment facilities and modes of care for mothers with PPD.